Analyses of genetic diversity and population structure of sesame (Sesamum indicum L.) germplasm collections through seed oil and fatty acid compositions and SSR markers - Teklu, D.H.; Shimelis, Hussein; Abebe, A.T.; Shayanowako, A.I.T. (Elsevier, 2022)
Knowledge of the genetic profiles of diverse germplasm collections of sesame using seed oil, fatty acid contents, and molecular markers is a prerequisite to develop market-preferred cultivars with quantity and quality oil. The objective of this study was to determine the genetic diversity and relationships among Ethiopia’s sesame germplasm collections using seed oil content and fatty acid compositions and diagnostic simple sequence repeat (SSR) markers to select genetically complementary and promising parental lines for breeding. The contents of the seed oil and fatty acids of 100 lines grown under field conditions were determined using the near-infrared reflectance spectrometry. Twenty-seven polymorphic SSR markers were used to assess the genetic profile of the test lines and complement the seed oil and fatty acid data. The SSR markers revealed that the mean gene diversity and polymorphic information content were 0.30 and 0.25, respectively. Population structure analysis identified four major heterotic groups. Based on higher oil content and desirable fatty acid compositions and SSR markers the following superior and complementary lines such as: Hirhir Kebabo Hairless Sel-6 (from sub-cluster I-b), Hirhir Humera Sel-8 and NN0058–2 (sub-cluster II-a) and Bawnji Fiyel Kolet (sub-cluster II-b) are identified for sesame breeding programs or production globally.